2006
DOI: 10.1074/jbc.m512630200
|View full text |Cite
|
Sign up to set email alerts
|

Importin-β Mediates Cdc7 Nuclear Import by Binding to the Kinase Insert II Domain, Which Can Be Antagonized by Importin-α

Abstract: We investigated the nuclear import mechanism of Cdc7, which is essential for the initiation of DNA replication. Here we report that importin-␤ binds directly to Cdc7 via the Kinase Insert II domain, promoting its nuclear import. Although both importin-␣ and -␤ bind to Cdc7 via the Kinase Insert II domain in a mutually independent manner, the binding affinity of Cdc7 for importin-␤ is ϳ10 times higher than for importin-␣ at low protein concentrations of an equimolar ratio. Immunodepletion of importin-␤, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…Therefore, it was previously suggested that kinase inserts may play regulatory functions (15). Consistent with this prediction, we reported previously that importin-␤ binds to Cdc7 at its Kinase Insert II and induces Cdc7 import into the nucleus (19).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Therefore, it was previously suggested that kinase inserts may play regulatory functions (15). Consistent with this prediction, we reported previously that importin-␤ binds to Cdc7 at its Kinase Insert II and induces Cdc7 import into the nucleus (19).…”
supporting
confidence: 69%
“…Cells grown on a glass coverslip were transfected with plasmids using Lipofectamine PLUS TM as suggested by the supplier (Invitrogen). Plasmid Constructs-The pEGFP⅐huCdc7 recombinant plasmid was constructed by cloning a full-length cDNA encoding the entire human Cdc7 into the SmaI site of pEGFP-C1 (Clontech) (19). Various Cdc7 deletion mutants were generated by PCR-based cloning using pfu DNA polymerase (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently found that PCNA contains a nuclear localization sequence (NLS) within the amino acid 101-120 segment [35], and its nuclear import appears to be mediated by importin b as PCNA binds to importin-b, but not importin-a [36]. These data suggest that cells have an active mechanism for the cytoplasmic localization of PCNA, which is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…52 For the resolution of Cdc7 phospho-isoforms, sample buffer was supplemented with 8M urea and SDS-PAGE was carried out utilizing a 10% resolving gel and at least 1 cm 3% stacking gel, run at 125 volts for 2.5 h to maximize resolution. Representative images of at least two independent experiments are shown.…”
Section: Western Blot Analysismentioning
confidence: 99%